The internship [videorecording (DVD)] - Levy, Shawn, 1968-; Vaughn, Vince; Wilson, Owen, 1968-; Byrne, Rose; Minghella, Max, 1985-
Trying to reboot their obsolete careers, old-school salesmen Billy and Nick talk their way into an internship program at the state-of-the-art Google campus, vying for a handful of spots among tech-savvy college students who are half their age and twice as smart. The competition is fiercely funny as Billy and Nick break all the rules in a hilarious quest to land their dream jobs.